2022
DOI: 10.1002/2211-5463.13422
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into Charcot–Marie–Tooth disease‐linked mutations in human GDAP1

Abstract: Charcot-Marie-Tooth disease (CMT) is the most common inherited peripheral polyneuropathy in humans, and its different subtypes are linked to mutations in dozens of different genes. Mutations in gangliosideinduced differentiation-associated protein 1 (GDAP1) cause two types of CMT, demyelinating CMT4A and axonal CMT2K. The GDAP1-linked CMT genotypes are mainly missense point mutations. Despite clinical profiling and in vivo studies on the mutations, the etiology of GDAP1-linked CMT is poorly understood. Here, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(41 citation statements)
references
References 86 publications
(132 reference statements)
11
26
0
Order By: Relevance
“…Building upon earlier work on GDAP1 structure [1012], we focused here on several CMT-linked variants that reside on different secondary structure elements on the GDAP1 crystal structure. While we earlier specifically looked at R120W and H123R on helix α3 [12], here we produced and characterised the variants R120Q, R161H, A247V, H256R, R282H, R310Q, and R310W. The stability and solution structure were studied for all variants, while crystal structures were determined for three of them: R120Q, A247V, and R282H.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Building upon earlier work on GDAP1 structure [1012], we focused here on several CMT-linked variants that reside on different secondary structure elements on the GDAP1 crystal structure. While we earlier specifically looked at R120W and H123R on helix α3 [12], here we produced and characterised the variants R120Q, R161H, A247V, H256R, R282H, R310Q, and R310W. The stability and solution structure were studied for all variants, while crystal structures were determined for three of them: R120Q, A247V, and R282H.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of CMT-linked missense mutations in GDAP1 are located within the vicinity of the hydrophobic clusters of the GST-like domains and the dimer interface [11], and the variants may induce changes in intramolecular hydrogen bonding networks [12]. In addition to the R120W and H123R studied earlier [12], we now determined three new mutant crystal structures: R120Q, A247V, and R282H. These mutations reside in helices α3 (R120Q), α7 (A247V), and α8 (R282H), which are core elements of the GDAP1 fold.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Not only do the various sequence variants contribute to the phenotype, but genetic interaction between two alleles of GDAP1 is important for the genetic load. Even the variant p.Glu222Lys seems to be weak in recent studies studying the interaction of the amino-acid GDAP1 residues, and the authors showed that the Glu222Lys residue is sandwiched between three Arg side chains (Arg120, Arg225, Arg226) and Tyr124, and, additionally, this residue has van der Waals contacts to Leu239, the amino acid residue most frequently substituted in CMT4A [ 24 ]. This implies the importance of Glu222 amino acid residue in maintaining the proper structure of GDAP1 protein, and importantly its substitution can affect Leu239Phe residue.…”
Section: Discussionmentioning
confidence: 99%